Arsenic concentration in water, rice straw and cow milk – A micro level study in West Bengal - Sarkar, Prabin; Ray, Pinaki Ranjan; Ghatak, Pijuskanti; Sen, Munmun (Indian Journal of Dairy Science, 2016)
Arsenic poisoning of water is severe in West Bengal and eight of the twenty districts have reported to have ground water arsenic contamination above the recommended level of WHO. Long term use of arsenic contaminated fodder and water by milch animals may result in the increase of arsenic concentration in raw milk. Arsenic concentration of irrigation water, drinking water , rice straw and raw cow milk collected from the eight villages of Haringhata and Chakdaha block were studied by Flow Injection Hydride(FIH) atomic absorption spectrophotometric method. The average arsenic concentration of irrigation water, drinking water and rice straw were found to be 0.53+ 0.006 mgl-1 , 0.22+ 0.007 mgl-1 and 2.84+ 0.033 mg kg-1 respectively which was well above the permissible limit of 0.10 mgl-1 prescribed by FAO for irrigation water and 0.01mgl-1 prescribed by WHO for Drinking water. Cow milk collected from the experimental area also showed average arsenic concentration of 0.069+ 0.003 mgl-1 which is less than the FSSAI recommended maximum level of 0.10 mgl-1. Arsenic concentration of cow milk related significantly with the arsenic concentration of drinking water, rice straw and irrigation water.